Phosphorus and Micronutrient Status in Paddy Soils from Jogjakarta, Indonesia. - Hanudin, Eko; Widya Yuwono, Nasih; Betty Widyastuti, Ika; Widyati, Lilis (2009)
The content and distribution of P (available and potential) vertically and horizontally in the intensive paddy field already reached a high-very high rate. The content of the P fractions in the plowed layer from the 6 study areas as follow: 1). P-saloid: Moyudan > Sedayu > Sanden > Godean > Lendah > Sentolo; 2). Al-P: Godean > Moyudan > Sedayu > Sentolo > Sanden > Lendah; 3). Fe-P : Moyudan > Godean > Sedayu > Lendah > Sentolo > Sanden; 4). Ca-P: Godean > Sentolo > Lendah > Moyudan > Sedayu > Sanden; 5). P-reducted: Sanden > Sentolo > Lendah > Moyudan > Sedayu > Godean; 6). P-occluded: Sentolo > Sanden > Lendah > Godean = Moyudan > Sedayu, respectively. Whereas, the distribution of the P fractions in the subsoil layer as followed: 1). P-Saloid: Godean > Sedayu > Sentolo > Moyudan = Lendah > Sanden; 2). Al-P: Godean > Moyudan > Sedayu > Sentolo > Sanden > Lendah; 3). Fe-P: Godean > Moyudan > Sedayu > Lendah > Sanden > Sentolo; 4). Ca-P: Godean > Lendah > Sedayu > Moyudan > Sentolo > Sanden; 5). P-reducted: Sanden > Moyudan > Lendah > Godean > Sedayu > Sentolo; 6). P-occluded: Lendah > Sanden > Sentolo > Sedayu > Moyudan = Godean. The mentioned P fractions are not available for plant growth. The concentration of Zn and Cu in the paddy soils were catagorized as a moderate level. It means that the both micronutrients were found to be sufficient for plant growth. This finding implied that the excessive amount of soil-P did not decrease significantly the Zn and Cu availabily. However, the amount of fulvic acid in the soil may have a contribution to the Zn and Cu availability.